The book of Leviticus : composition and reception - Rendtorff, Rolf, 1925-; Kugler, Robert A.; Bartel, Sarah Smith. (Vetus Testamentum, Supplements, 2003)
This volume examines the formation, final form, themes, and interpretation of the Book of Leviticus. Contributors include well-known experts on Leviticus: Baruch Levine, Jacob Milgrom, Graeme Auld, Andreas Ruwe, and James Watts address Leviticus in its compositional and literary context; Alfred Marx, Mary Douglas, Walter Houston, and Adrian Schenker treat issues of cult and sacrifice; and Rene Peter-Contesse, Lester Grabbe, and Calum Carmichael discuss Leviticus on the priesthood. A groundbreaking section on Leviticus in translation and interpretation includes essays by Sarianna Metso and Eugene Ulrich, Martin McNamara, David Lane, Peter Flint, Robert Kugler, Bruce Chilton, Hannah Harrington, Gerhard Bodendorfer, Linda Schearing, and Judith Romney Wegner. These essays will serve students of Leviticus well for long time to come.